The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s10162-018-00710-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Musical Training and Hearing Loss on Fundamental Frequency Discrimination and Temporal Fine Structure Processing: Psychophysics and Modeling

Abstract: Several studies have shown that musical training leads to improved fundamental frequency ( F 0 ) discrimination for young listeners with normal hearing (NH). It is unclear whether a comparable effect of musical training occurs for listeners whose sensory encoding of F 0 is degraded. To address this question, the effect of musical training was investigated for three groups of listeners (young NH, older NH, and older listeners with hearing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 70 publications
2
29
0
Order By: Relevance
“…We did not find evidence of age effects on F0 discrimination of unresolved complex tones in the current study, consistent with the results of Bianchi, Carney, Dau, Santurette, 2019 . Although our results rule out the hypothesis that age per se may have large effects on F0 discrimination of unresolved complex tones, the CIs for the age effect were not very narrow, and are compatible with the possibility that small age effects exist but were not detected in the current study.…”
Section: Discussionsupporting
confidence: 90%
“…We did not find evidence of age effects on F0 discrimination of unresolved complex tones in the current study, consistent with the results of Bianchi, Carney, Dau, Santurette, 2019 . Although our results rule out the hypothesis that age per se may have large effects on F0 discrimination of unresolved complex tones, the CIs for the age effect were not very narrow, and are compatible with the possibility that small age effects exist but were not detected in the current study.…”
Section: Discussionsupporting
confidence: 90%
“…Bianchi et al. (2019) observed that both NH and HI musicians with at least 8 years of formal music education showed lower IPD FLs than nonmusicians.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, we adopted a training paradigm that has been used in many previous studies exploring IPD discrimination with tone sequence stimuli (e.g., Bianchi et al., 2019; Füllgrabe et al., 2017; Hopkins & Moore, 2011; Neher et al., 2011): IPD cues were initially replaced with ILD cues, because ILD cues presumably result in more discriminable lateralization for all participants, in particular for older HI listeners. However, Ortiz and Wright (2010) found that, in order to improve NH listeners’ ITD discrimination performance, training based on ITD discrimination proved more effective than ILD discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that musical training is associated with improved speech perception in noise 13 , and that the benefit of musical training may protect against some of the deleterious effects of age on speech perception in noise 4 . However, although it is generally accepted that musical training is associated with improved skills relevant for music, such as pitch discrimination 59 , pitch interval discrimination 10,11 and rhythm discrimination 12,13 , its association with speech perception in noise and other challenging conditions remains disputed because of several failures to find such an effect 7,8,14,15 .…”
Section: Introductionmentioning
confidence: 99%